4(-3x+1)+2(5x-3)=

Simple and best practice solution for 4(-3x+1)+2(5x-3)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(-3x+1)+2(5x-3)= equation:


Simplifying
4(-3x + 1) + 2(5x + -3) = 0

Reorder the terms:
4(1 + -3x) + 2(5x + -3) = 0
(1 * 4 + -3x * 4) + 2(5x + -3) = 0
(4 + -12x) + 2(5x + -3) = 0

Reorder the terms:
4 + -12x + 2(-3 + 5x) = 0
4 + -12x + (-3 * 2 + 5x * 2) = 0
4 + -12x + (-6 + 10x) = 0

Reorder the terms:
4 + -6 + -12x + 10x = 0

Combine like terms: 4 + -6 = -2
-2 + -12x + 10x = 0

Combine like terms: -12x + 10x = -2x
-2 + -2x = 0

Solving
-2 + -2x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2' to each side of the equation.
-2 + 2 + -2x = 0 + 2

Combine like terms: -2 + 2 = 0
0 + -2x = 0 + 2
-2x = 0 + 2

Combine like terms: 0 + 2 = 2
-2x = 2

Divide each side by '-2'.
x = -1

Simplifying
x = -1

See similar equations:

| -5.4=a+2.2 | | x+25+2x=-1-2x-4 | | -14=7x-5x+14 | | h=1wh | | 58-3x=6x+24 | | 9n-20+4n=7n+16 | | 60+7x=13x-8 | | 9-2y=y+2(4y-5) | | 4n-5(n+2)=7-3(3-n) | | 67+92x=92 | | 2/4+2/4+x=3 | | 4/3=5/8a+14/3 | | -5x-3(3x+10)=138 | | -3(2x-3)=4(5-x) | | 2(3z-1)=16 | | 3(x-8)=7 | | 3x+8x-14=30 | | 3(x-4)+37=2x | | 1.3y+7.8=1.3 | | 5x-6=5*5+3 | | -4w+4=0 | | 6x+2-3x+9=0 | | x/2+x/3*4=5 | | -2x-6(3x+10)=40 | | 14+2y=2(y+3) | | (5x-4)(3x+2)=0 | | 100+10=x+15 | | 7(x+4)+8=8(2x-6) | | 5r=16-(2r+8) | | 9-x+2=2x+3x | | 4x-4(x+4)=5(x+4) | | 2(3(-3)-2)+-3=9 |

Equations solver categories